Outbreak of Neisseria meningitidis, Edmonton, Alberta, Canada - Gregory J. Tyrrell; Linda Chui; Marcia Johnson; Nicholas Chang; Robert P. Rennie; James A. Talbot (Emerging Infectious Diseases, 2002)
From December 1999 to April 2001, the greater Edmonton region had 61 cases of invasive meningococcal infection, two fatal. The outbreak was due to Neisseria meningitidis serogroup C, electrophoretic type 15, serotype 2a. Analysis of the strains showed that 50 of 56 culture-confirmed cases were due to a single clone and close relatives of this clone. This strain had not been previously identified in the province of Alberta dating back to January 1997